Pengaruh Mobilisasi Dini terhadap Involusi Uterus pada Ibu Post Partum di Wilayah Kerja Puskesmas O Mangunharjo Kabupaten Musi Rawas - Nuril Absari; Desty Nova Riyanti (Jurnal Kebidanan Harapan Ibu Pekalongan, 2020)
The purpose of this study is to determine Effect of Early Mobilization to Involution Utery on Postpartum mother in Area of O Mangunharjo Primary Health Care MusiRawasDistrict.This study used pre experiment (The static group comparation design). Population in this study were all Postpartum mother in Area of O Mangunharjo Primary Health Care MusiRawas District in month of July-August 2018 obtained 30 sample consist of 15 people doing Early Mobilization and 15 did not doing Early Mobilization. Collecting data in this study used primary data with spreaded questionnaire. Data analysis used normality data, Independent samples T Test.The result of this study showed: (1) Obtained value average decreased Involution Utery on group who were doing Early Mobilization were 8,02 days (2) Obtained value average decreased Involution Utery on group who were doing Early Mobilization were 9,65 days 93) there is Effect of Early Mobilization to Involution Utery on Postpartum mother in Area of O Mangunharjo Primary Health Care MusiRawas District.